De Morgan's laws


THEOREM    \(\neg(P \wedge Q) \dashv\vdash \neg P \vee \neg Q\)

Proof available

THEOREM    \(\neg(P \vee Q) \dashv\vdash \neg P \wedge \neg Q\)

Proof available

THEOREM    \(A \cup (B \cap C) = (A \cup B) \cap (A \cup C)\)

Proof unavailable

THEOREM    \(\neg P \wedge \neg Q \vdash \neg (P \vee Q)\)

Proof available

THEOREM    \(\neg (P \vee Q) \vdash \neg P \wedge \neg Q\)

Proof available

THEOREM    \(\neg P \vee \neg Q \vdash \neg (P \wedge Q)\)

Proof available

THEOREM    \(\neg (P \wedge Q) \vdash \neg P \vee \neg Q\)

Proof available